Parasympathetic preganglionic cardiac motoneurons labeled after voluntary diving - Panneton, W Michael; Anch, Michael; Gan, Qi; Panneton, Whitney M. (Frontiers in Physiology, 2014)
A dramatic bradycardia is induced by underwater submersion in vertebrates. The location of parasympathetic preganglionic cardiac motor neurons driving this aspect of the diving response was investigated using cFos immunohistochemistry combined with retrograde transport of cholera toxin subunit B (CTB) to double-label neurons. After pericardial injections of CTB, trained rats voluntarily dove underwater, and their heart rates dropped immediately to 95±2bpm, an 80% reduction. After immunohistochemical processing, the vast majority of CTB labeled neurons were located in the reticular formation from the rostral cervical spinal cord to the facial motor nucleus, confirming previous studies. Labeled neurons caudal to the rostral ventrolateral medulla were usually spindle-shaped aligned along an oblique line running from the dorsal vagal nucleus to the ventrolateral reticular formation, while those more rostrally were multipolar with extended dendrites. Nine percent of retrogradely-labeled neurons were positive for both cFos and CTB after diving and 74% of these were found rostral to the obex. CTB also was transported transganglionically in primary afferent fibers, resulting in large granular deposits in dorsolateral, ventrolateral, and commissural subnuclei of the nucleus tractus solitarii and finer deposits in lamina I and IV-V of the trigeminocervical complex. The overlap of parasympathetic preganglionic cardiac motor neurons activated by diving with those activated by baro- and chemoreceptors in the rostral ventrolateral medulla is discussed. Thus the profound bradycardia seen with underwater submersion reinforces the notion that the mammalian diving response is the most powerful autonomic reflex known.